Tattoo reaction: Case series - Muneer Mohamed; Kindy Darilyn Anderson Sohkhlet; Aneesh Samayam (Our Dermatology Online, 2018)
Tattoo is going to be a very common practice especially among young people and we are witnessing a gradual increase of numerous potential complications to tattoo placement which are often seen by physicians, but generally unknown to the public. The most common skin reactions to tattoo include a transient acute inflammatory reaction due to trauma of the skin with needles and medical complications such as superficial and deep local infections, systemic infections, allergic contact dermatitis, photodermatitis, granulomatous and lichenoid reactions, and skin diseases localized on tattooed area (eczema, psoriasis, lichen, and morphea). In this series we present three cases of tattoo reaction.